2016
DOI: 10.5812/aapm.26714
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Dexmedetomidine and Fentanyl as Adjuvant to Bupivacaine on Duration of Spinal Block in Addicted Patients

Abstract: Background:Addicted patients have innate tolerance to local anesthetics in both neuraxial and peripheral blocks. Dexmedetomidine (Dex) is a highly selective α2 adrenergic receptor agonist used as additive to increase quality and duration of peripheral nerve blocks.Objectives:The current study aimed to compare the effect of dexmedetomidine and fentanyl additives on bupivacaine to prolong the duration of block and minimizing side effects.Patients and Methods:Patients were candidates for elective surgery less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
13
17
0
Order By: Relevance
“…These findings clearly states that dexmedetomidine as an adjuvant provided prolonged sensory and motor duration compared to fentanyl as an adjuvant to hyperbaric bupivacaine. Similar findings was also observed by Khan et al [1] , Gupta R et al [20] The onset times observed conducted by AI Ghanem et al [10 dexmedetomidine than those observed attributed by difference in patient supine in our study).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings clearly states that dexmedetomidine as an adjuvant provided prolonged sensory and motor duration compared to fentanyl as an adjuvant to hyperbaric bupivacaine. Similar findings was also observed by Khan et al [1] , Gupta R et al [20] The onset times observed conducted by AI Ghanem et al [10 dexmedetomidine than those observed attributed by difference in patient supine in our study).…”
Section: Discussionsupporting
confidence: 92%
“…Similar Gupta et al, Mehendru V et al [18] Heart rate (HR), mean arterial blood pressure (MAP) baseline, just after dural puncture, 15min, then at 5min intervals at 5min intervals at till Though there was theoretical possibility [22] , difference of HR was not statistically the above intervals. Similar results Khan et al, [1] Suresh et al, [23] and Statistically significant lowering Licensed Under Creative Commons Attribution CC BY [14] , Mehendru V et al [18] , Kishore et al [19] , ] , Safari et al [20] , Suresh et al [23] , Sunil BV et al [24] , Nayagam HA et al [25] and Routrey et al [26] The mechanism by which intrathecal α adrenoreceptor agonists prolong the motor and sensory block of local anaesthetics is at the best, speculative. It may be an additive or synergistic effect secondary to the different mechanisms of action of the local anaesthetics and intrathecal α adrenoreceptor agonists.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations